UPAYA MENINGKATKAN MINAT MASYARAKAT SEKOLAH DI MTS MUHAMMADIYAH JAYAPURA MELALUI PROMOTION MIX - Sugiyantoro Sugiyantoro (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
Since Madrasah Tsanawiyah (MTs) Muhammadiyah Jayapura was established in 2006 the number of new learners who enroll very little, the number is still below the minimum standards set by the government. From year to year did not experience a significant increase, even in a certain year it has decreased. Thus its existence is threatened, it is feared will experience fate like some other MTs in Jayapura City which naturally closed because do not have learners. This study aims to increase the interest of the school community in MTs Muhammadiyah Jayapura through promotion mix. The method used in this research is action research. The results showed that the promotion mix has an important role in increasing the interest of the school community in MTs Muhammadiyah Jayapura